VEXAS syndrome: lessons learnt from an early Australian case series. Issue 4 (13th April 2022) - Islam, Sadia; Cullen, Taylor; Sumpton, Daniel; Damodaran, Arvin; Heath, David; Bosco, Annmarie; Doo, Nicole W.; Kidson‐Gerber, Giselle; Cheong, Anthony; Lawford, Ron; Walsh, Rebecca; Sammel, Anthony
Abstract: VEXAS is a newly recognised adult‐onset autoinflammatory syndrome resulting from a somatic mutation in the UBA1 gene. Herein, we present three cases of VEXAS syndrome in Sydney, Australia, that capture key clinical features and the refractory nature of the condition. They highlight the importance of multidisciplinary collaboration for early diagnosis and the need for new therapeutic options.